A chemometrics approach to analyze volatile molecules released by post-mortem bovine fast-twitch muscles. Issue 3 (2nd July 2016) - Acevedo, Cristian A.; Tomic, Gerda; Santander, Rocío; Creixell, Werner; Osorio, Felipe; Sánchez, Elizabeth
ABSTRACT: It is well known that beef produces volatile molecules. In this work, the detection of volatiles released by post-mortem bovine fast-twitch muscles ( Musculus longissimus dorsi and Musculus cutaneus trunci ) was done using GC/MS–SPME (gas chromatography/mass spectrum–solid-phase microextraction). The releases of volatile molecules were modeled against three factors ( rigor-mortis, animal age and oxidative capacity) using a chemometrics approach (experimental design and partial least squares regression). The GC/MS–SPME technique produced more than 30 reproducible chromatographic peaks, but only 13 were associated significantly with two factors ( rigor-mortis and animal age). The volatile profile was composed mainly of alcohols, aldehydes and alkanes. The factor "animal age" was the main variable related to the release of volatile molecules. The results strongly suggest that the release of volatile molecules change according to post-mortem metabolism and the animal age.